A study on the relationship between employee's workplace attitudes and intention to turnover at MISC Berhad / Noor Arbaah Abdul Mutalef - Abdul Mutalef, Noor Arbaah (Faculty of Business and Management, 2007)
The purpose of the present study is to examine the four dimensions of workplace attitudes such as job involvement, job satisfaction, career satisfaction, and organizational commitment will influence and have relationship with intention to stay among employees at MISC Berhad, Kuala Lumpur. Therefore, the proposed research framework and hypotheses were developed with the intention of examining this relationship. In this study, descriptive research was conducted to obtain the information needed. It involved acquiring primary data, preparing questionnaires, sampling method and deciding on how variables will be measured and analyzed. This study was conducted at MISC Berhad, Jalan Sultan Hishamuddin, Kuala Lumpur. After conducted this study, the results revealed that where four dimensions of employee's workplace attitudes have significant relationship with intention to stay among employees at MISC Berhad. The main factor to determine the intention to stay among employees is career satisfaction where the p-value is 0.01.The researcher has come out with several recommendations that MISC Berhad can use for future plan, monitor workplace attitudes and to evolve better management practices. Thus, employees' intention to stay is maintained at high level.